2015
DOI: 10.1007/s00261-015-0475-z
|View full text |Cite
|
Sign up to set email alerts
|

A novel semi-automatic segmentation method for volumetric assessment of the colon based on magnetic resonance imaging

Abstract: Regional colon volumes were comparable to previous findings using fully manual segmentation. The method showed good agreement between observers and may be used in future studies of gastrointestinal disorders to assess colon and fecal volume and colon morphology. Novel insight into morphology and quantitative assessment of the colon using this method may provide new biomarkers for constipation and abdominal pain compared to radiography which suffers from poor reliability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 31 publications
0
28
0
Order By: Relevance
“…The 'large bowel' hypothesis proposes that rapid colonic fermentation of unabsorbed carbohydrates generates gas, distending the colon and causing flatulence, bloating and discomfort. Reports that some IBS patients have different microbiota to non-sufferers 10,11 , and that the microbiota changes with diet, 12,13 20,21 . Luminal gas has been assessed in both the small bowel 22 and colon 23 .…”
Section: Discussionmentioning
confidence: 99%
“…The 'large bowel' hypothesis proposes that rapid colonic fermentation of unabsorbed carbohydrates generates gas, distending the colon and causing flatulence, bloating and discomfort. Reports that some IBS patients have different microbiota to non-sufferers 10,11 , and that the microbiota changes with diet, 12,13 20,21 . Luminal gas has been assessed in both the small bowel 22 and colon 23 .…”
Section: Discussionmentioning
confidence: 99%
“…16 The present study will not elaborate on software (Colometry v.1.0, MechSense, Aalborg University Hospital, 2015, Aalborg, Denmark) details, but merely explain that the method is based on manually placed regions of interest on the T2-weighted scans. These regions of interest are used to outline the four colon segments in each of the 35-40 coronal slices per scan.…”
Section: Colorectal Volumesmentioning
confidence: 99%
“…On the other hand, our recent study with this method found that it exhibits negligible intra-observer bias. 16 Currently, the MRI-based method is not able to discern between the volume of the colon wall itself, fecal volume and or gas within the colon. Therefore, the colorectal volumes reported here are the total combined volume of the colon itself and all content (gas, fluid mass, solid mass).…”
Section: Study Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, chyme heterogeneity in the ascending colon has been assessed with subjective observer scores, and more objectively with imaging‐based feature analysis . Colonic segmental volumes can be quantified from T 2 ‐weighted MRI sequences, where the colon wall shows high contrast to surrounding fat tissue, a method with high reliability between observers . T 2 ‐weighted MRI has also been used to quantify the amount of free water pockets in the small bowel and colon after drinking water, due to the images' high signal strength corresponding to free water .…”
mentioning
confidence: 99%